PERANCANGAN KEMBALI ANTARMUKA APLIKASI BELI.IN MENGGUNAKAN METODE DESIGN SPRINT - Halim, Natalia Angelina Putri; Rahman, Syaiful; Bahri, Syamsul (KHARISMA Tech, 2024)
Beli.in is an application that provides services for daily needs and provides other services recommendations. This study aims to improve interface of the Beli.in application so that it will be more comfortable for application users. Design Sprint method used in this redesigning study and drawing conclusions with System Usability Scale (SUS). The design sprint method is done in five stages: understand, diverge, decide, prototype, and validate in five days. The results were tested back to the user with a questionnaire to show that the results of the new design have been well received by the user.